Nanoparticle electrocatalysis: Unscrambling illusory inhibition and catalysis - Kaetelhoen, F; Chen, L; Compton, R (Elsevier, 2019)
Voltammetry is ubiquitously used in the characterisation of new materials for electrocatalysis. It often sets at least the starting point of any analysis aiming to explore whether electrodes decorated with nano- or other particles feature advanced catalytic behaviour over their bare equivalents. Such analysis bears a substantial and entirely unexpected level of complexity as the mass transport inside the porous layer formed by the particles has a dramatic impact on the measurement. It is shown even for entirely inactive, non-conducting, and non-adsorbing particles, the voltammetry of any electrochemically reversible reaction necessarily varies both between seeming catalysis and apparent irreversible kinetics merely depending on the voltage scan rate. This effect arises from the superposition of thin layer effects and locally enhanced diffusive fluxes inside the porous material with the latter being reminiscent of convergent diffusion and leading to apparent electrochemically-irreversible reactions. While the relevance of thin layer effects in porous materials has been realised before, the seeming irreversible reactions and the understanding of them as result of the internal structure of the modifying layer are, to our knowledge, an entirely new finding. The presented results are counter-intuitive and yet essential for all voltammetric analysis of catalysis at nanostructured interfaces and at porous electrode materials.